2018
DOI: 10.1111/tid.12886
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole concentration is inversely correlated with corticosteroid usage in immunocompromised patients

Abstract: VRCZ might be metabolized by an enzyme induced by corticosteroid treatment; therefore, intraindividual variation in VRCZ metabolism should be considered prior to concurrent treatment, especially for patients with hematological malignancies treated with corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Drug-drug interactions also arise in this context. Dexamethasone was widely used in CAPA patients and induces CYP2C9, which could decrease the VTC [ 32 ]. Thus, therapeutic drug monitoring is a cornerstone for patient management, as we faced low concentrations of voriconazole in this series with a significant delay to reach the optimal therapeutic range in CAPA vs. IAPA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Drug-drug interactions also arise in this context. Dexamethasone was widely used in CAPA patients and induces CYP2C9, which could decrease the VTC [ 32 ]. Thus, therapeutic drug monitoring is a cornerstone for patient management, as we faced low concentrations of voriconazole in this series with a significant delay to reach the optimal therapeutic range in CAPA vs. IAPA patients.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study has identified glucocorticoid receptor binding sites in the promoter region of the CYP2C19 gene and demonstrated up‐regulation of CYP2C19, supporting an inductive effect of glucocorticoids on CYP2C19 . There are limited data regarding the interaction between voriconazole and corticosteroids in clinical practice . Dolton et al found that concomitant dexamethasone use was associated with a 3.75‐fold decrease in voriconazole concentrations .…”
Section: Dips Algorithm (Drug Interaction Probability Scale); the Intmentioning
confidence: 99%
“…In the present study, although radiological ndings were generally considered to not be suggestive of IPA during ARDS, a meticulous analysis showed several interesting differences between the images, with well-circumscribed nodules, tree in bud, and bronchial wall thickening, which were observed signi cantly more frequently in IAPA than CAPA patients. (31). Thus, therapeutic drug monitoring is a cornerstone for the patient management as we were faced in this series with low concentrations of voriconazole with a signi cant delay to reach the optimal therapeutic range in CAPA versus IAPA patients.…”
Section: Resultsmentioning
confidence: 98%
“…Drug-drug interactions also arise in this context. Dexamethasone was widely used in CAPA patients and induces CYP2C9, which could decrease the VTC (31). Thus, therapeutic drug monitoring is a cornerstone for the patient management as we were faced in this series with low concentrations of voriconazole with a signi cant delay to reach the optimal therapeutic range in CAPA versus IAPA patients.…”
Section: Resultsmentioning
confidence: 99%